No relation between Body Mass Index and neurocognitive recovery in abstinent alcohol dependent patients? - Jeroen Staudt; Yvonne Rensen; Hein De Haan; Boukje Dijkstra; Jos Egger (PLoS ONE, 2025)
Background Neurocognitive deficits in patients with Alcohol Use Disorder (AUD) may partially arise as a result from nutritional deficiencies. Previous studies have shown associations between nutritional deficiencies and impaired neurocognitive function, but the results are inconclusive. Difficulties with operationalization may play a role in this. This study examined whether nutritional deficiencies, reflected by Body Mass Index (BMI) at admission, predict neurocognitive functioning after six weeks of abstinence and recovery of neurocognitive functions. This was also examined for different groups of BMI (very low, normal and very high). Methods Data was derived from 86 patients who were diagnosed with AUD following DSM-5 criteria and referred for clinical detoxification and neuropsychological examination. At admission, BMI, demographic information, and information regarding alcohol use were derived from the medical record and a clinical interview. During the second and sixth week of admission patients underwent neuropsychological assessment using well normed and validated instruments. Both longitudinal data and cross-sectional data from the sixth week were used to examine neurocognitive recovery. Results BMI as a continuous and categorical measure predicted the score on two tasks measuring speed and visuomotor performance after six weeks of abstinence. No further relation between BMI with neurocognitive function or recovery of neurocognitive functions was found. Conclusions This study found tentative support for BMI to predict performance on speed and visuomotor functioning in AUD-patients. These results may partly support an inverted U-shape, in which a very low BMI is negatively related to the outcome. Given the influence of nutritional deficiencies on the development of neurocognitive disorders, there is a need for further research that takes into account a possible non-linear relationship between BMI and neurocognitive functions, using additional physical measures, to identify (past) nutritional deficiencies.